The adsorption kinetic and isotherm studies of metal ions (Co2+, Sr2+, Cs+) on Fe3O4 nanoparticle of radioactive importance - Do Quoc Hung; Luu Xuan Dinh; Nguyen Van Tung; Le Thi Mai Huong; Nguyen Thi Lien; Pham Thanh Minh; Thu-Huong Le (Results in Chemistry, 2023)
The release of radionuclide elements from nuclear, medical, research, and defense fields has become a serious environmental problem. Hence, the investigation of the adsorption kinetic and isotherm of metal ions (Co2+, Sr2+, and Cs+) which are commonly found in radioactive waste has been considered essential for radioactive contaminant removal process from aqueous environment. In this paper, the adsorption kinetic of three metal ions on Fe3O4 nanoparticle (Fe3O4 NPs) have been described by the pseudo-first-order, pseudo-second-order, Elovich, and Intra-particle diffusion models, while the adsorption isotherm have been described by the Langmuir, Freundlich, Dubinin-Radushkevich model, and Tempkin isotherm models. Comparing the correction coefficients (R2) of four adsorption kinetic models and four isothermal adsorption models, the adsorption kinetic of three ions fitted well to the pseudo-second-order model with R2 > 0.9913. Meanwhile, the adsorption isotherm of three metal ions indicate that the Langmuir model was best fit the isothermal adsorptions with R2 > 0.9799. The maximum adsorption capacities of Co2+, Sr2+, and Cs+ were found to be 30.488, 34.843, and 33.223 mg/g, respectively. Based on the data of the present investigation, the Fe3O4 NPs being eco-friendly and low-cost adsorbent might be a suitable alternative for the elimination of radioactive waste from environmental and industrial wastes.